Do persons with asymmetric hip pain or radiographic hip OA have worse pain and structure outcomes in the knee opposite the more affected hip? Data from the Osteoarthritis Initiative. Issue 3 (March 2016) - Joseph, G.B.; Hilton, J.F.; Jungmann, P.M.; Lynch, J.A.; Lane, N.E.; Liu, F.; McCulloch, C.E.; Tolstykh, I.; Link, T.M.; Nevitt, M.C.
Summary: Purpose: To determine if asymmetry between hips in pain or radiographic osteoarthritis (RHOA) is associated with worse pain and joint space narrowing (JSN) at baseline and longitudinally in knees contralateral to more affected hips. Methods: We studied 279 participants in the Osteoarthritis Initiative with baseline asymmetry between hips in pain and 483 with asymmetry in RHOA none of whom had a hip replacement for ≥4 years after baseline. RHOA assessed from pelvis radiographs was categorized as none, possible or definite and hip pain on most days of a month in the past year as present/absent. Knee pain (WOMAC scale) and JSN (fixed flexion radiographs) were categorized as none, mild and moderate-severe. We compared knees contralateral and ipsilateral to more affected hips on baseline knee pain and JSN using clustered multinomial regression and on change in knee pain and JSN over 4–5 years using generalized linear and logistic estimating equations. Results: Knees contralateral to painful hips had less baseline pain ("moderate-severe" vs "none", relative risk ratio [RRR]: 0.39, 95% CI = 0.27–0.57), but greater baseline JSN ("moderate-severe" vs "none", RRR: 1.62, 95% CI = 1.09–2.38) and greater worsening of pain during follow-up ( P  = 0.001). Knees contralateral to hips with worse RHOA had nonsignificant trends for greater baseline JSN ( P  = 0.10) and JSN progression ( P  = 0.17). Conclusion: These findings provide limited support for the hypothesis that early asymmetry in hip pain and RHOA is associated with worse pain and structural outcomes in knees contralateral to the more affected hip.